Linking Gaming Disorder Tendencies in Children to Their Personality and Parental Gaming Behavior - Wernicke, Jennifer; Montag, Christian (Frontiers in Psychiatry, 2022)
Playing computer and video games (so-called gaming) is of great popularity among children and adults. But for some people, gaming gets out of hand and can result in a Gaming Disorder (GD). Among others, high neuroticism and low conscientiousness are considered to play a role in the etiology of GD. Next to personality traits, environmental variables are debated such as the parental influence on children's gaming behavior. In detail, parental gaming behavior could have role model functions for children. Based on empirical observations and theoretical frameworks, it was hypothesized that higher tendencies to GD in children are associated with higher neuroticism, lower conscientiousness, and higher parental tendencies to GD. In an online survey N = 493 parents (n = 472 females; age: M = 36.30, SD = 5.46) rated their own and their children's (n = 233 girls, n = 260 boys; age: M = 6.03, SD = 2.30) tendencies to GD by the Gaming Disorder Test (GDT) and their children's personality by the Big Five Inventory (BFI). Neuroticism was significantly correlated with the GDT scores of boys (rho = 0.256, p = 0.001) and girls (rho = 0.300, p = 0.001), while a significant correlation with conscientiousness was only present for boys (rho = −0.196, p = 0.010). Parents' and children's general playing of computer and video games were interdependent [χ2(1) = 29.14, p < 0.001]; hence, if parents reported to be gamers, their children were more likely gamers as well. The GDT scores of parents and children were positively correlated (boys: rho = 0.36; p = 0.002; girls: rho = 0.33, p = 0.004). The results indicate that already in children the personality traits neuroticism and conscientiousness are associated with tendencies toward GD. Moreover, as gaming of parents and children was related to each other, it is conceivable that parents influence their children's gaming behavior via their own gaming behavior. Therefore, parents should be aware of their exemplary function for children and may overthink their own gaming behavior. But it has to be mentioned that the correlational nature of the present work allows no insights regarding causal relations.